2017
DOI: 10.3390/v9030061
|View full text |Cite|
|
Sign up to set email alerts
|

Emerging Interaction Patterns in the Emiliania huxleyi-EhV System

Abstract: Viruses are thought to be fundamental in driving microbial diversity in the oceanic planktonic realm. That role and associated emerging infection patterns remain particularly elusive for eukaryotic phytoplankton and their viruses. Here we used a vast number of strains from the model system Emiliania huxleyi/Emiliania huxleyi Virus to quantify parameters such as growth rate (µ), resistance (R), and viral production (Vp) capacities. Algal and viral abundances were monitored by flow cytometry during 72-h incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 109 publications
0
12
0
Order By: Relevance
“…Also, experimental data on the host range of EhV99B1 and EhV207 showed that, out of an array of 16 different E. huxleyi strains, they successfully infected 12 and 8, respectively (Table S3). EhV86 was also recently shown to have a broader host range than EhV207 (33 strains vs 27 strains, respectively for a slow:fast infectivity ratio of 1.2; Ruiz et al, 2017), further supporting this idea. Our host-range experiments yielded a slow:fast infectivity ratio of~1.5 (75%:50%), which was subsequently used as an empirically derived parameter to inform the model.…”
Section: Ecological Scenarios Of Ehv Infectionmentioning
confidence: 76%
“…Also, experimental data on the host range of EhV99B1 and EhV207 showed that, out of an array of 16 different E. huxleyi strains, they successfully infected 12 and 8, respectively (Table S3). EhV86 was also recently shown to have a broader host range than EhV207 (33 strains vs 27 strains, respectively for a slow:fast infectivity ratio of 1.2; Ruiz et al, 2017), further supporting this idea. Our host-range experiments yielded a slow:fast infectivity ratio of~1.5 (75%:50%), which was subsequently used as an empirically derived parameter to inform the model.…”
Section: Ecological Scenarios Of Ehv Infectionmentioning
confidence: 76%
“…Insights into virus-host specificity have also been gained from studies on closely related viruses. A cross-infection network between coccolithovirus and Emiliania huxleyi strains showed a nested host-virus interaction pattern where more resistant hosts are only infected by viruses with broader host range, suggesting strong coevolution in host-virus system [ 85 ]. At a larger scale, phylogenetic correspondence has been observed between three genera of Mamiellales (“Prasinophyceae”, Chlorophyta) and their prasinoviruses [ 44 ].…”
Section: Variation and Evolution Of Host Rangementioning
confidence: 99%
“…The material costs of the viruses (i.e., virus × burst size) is so small set against the metabolic costs normally incurred by the host in cell replication every day or so, that any additional cost in virus evolution would most likely be minor (see also Figures 1B, 2E). Evolution of viruses is also matched by evolution of resistance in the host (Ruiz et al, 2017), a process that itself may cost the host little to achieve (Thingstad et al, 2014), especially when set against all other metabolic costs (Heath et al, 2017).…”
Section: Traitsmentioning
confidence: 99%